Pendampingan dalam Program Bimbel Cendekia Untuk Meningkatkan Motivasi Belajar Anak di Dukuh Dayakan Wagir Lor - Zakiyah; Syamsul Muqorrobin (Social Science Academic, 2025)
Every country strives to provide high-quality education to prepare for the era of progress. However, the learning process at school alone is not enough to maximize children's motivation to learn. One way to increase this motivation is through tutoring. The goal of this program is to help students, especially early childhood and elementary school students, achieve optimal learning, particularly through home-based or in-person learning. The method used in this activity is the ABCD (Asset-Based Community Development) method. The results of this program include increased interest in learning in children, increased confidence in completing school assignments independently, and increased enthusiasm and interest in learning.